Molecular Signature of Nitroso–Redox Balance in Idiopathic Dilated Cardiomyopathies. Issue 9 (22nd September 2015) - Menazza, Sara; Aponte, Angel; Sun, Junhui; Gucek, Marjan; Steenbergen, Charles; Murphy, Elizabeth
Abstract : Background: Idiopathic dilated cardiomyopathy is one of the most common types of cardiomyopathy. It has been proposed that an increase in oxidative stress in heart failure leads to a decrease in nitric oxide signaling, leading to impaired nitroso–redox signaling. To test this hypothesis, we investigated the occurrence of protein S‐nitrosylation (SNO) and oxidation in biopsies from explanted dilated cardiomyopathy and nonfailing donor male and female human hearts. Methods and Results: Redox‐based resin‐assisted capture for oxidation and SNO proteomic analysis was used to measure protein oxidation and SNO, respectively. In addition, 2‐dimensional difference gel electrophoresis using maleimide sulfhydryl‐reactive fluors was used to identify the SNO proteins. Protein oxidation increased in dilated cardiomyopathy biopsies in comparison with those from healthy donors. Interestingly, we did not find a consistent decrease in SNO in failing hearts; we found that some proteins showed an increase in SNO and others showed a decrease, and there were sex‐specific differences in the response. We found 10 proteins with a significant decrease in SNO and 4 proteins with an increase in SNO in failing female hearts. Comparing nonfailing and failing male hearts, we found 9 proteins with a significant decrease and 12 proteins with a significant increase. We also found an increase in S‐glutathionylation of endothelial nitric oxide synthase in failing female versus male hearts, suggesting an increase in uncoupled nitric oxide synthase in female hearts. Conclusion: These findings highlight the importance of nitroso–redox signaling in both physiological and pathological conditions, suggesting a potential target to treat heart failure.